Active fungal infections alter the respiratory microbiome profiles of Mayo Clinic Arizona patients - Kollath, Daniel R.; McAulay, Kathrine; Higgins Keppler, Emily A.; Reilly, Kenta S.; Sakata, Kenneth K.; Barker, Bridget M.; Grys, Thomas E. (Frontiers in Microbiomes, 2025)
IntroductionThe function of the respiratory microbiome during an active infection is not well characterized. Studies from the gut microbiome suggest a diverse community can aid in modulating the immune system to control infectious pathogens. MethodsTo determine if there are microbial community compositional changes in the human lung during an infection, we conducted an analysis of both the 16S rDNA and the Internal Transcribed Spacer (ITS) region of DNA from bronchoalveolar lavage fluid (BALF) of patients from Mayo Clinic Arizona. In addition to general classification, we assessed differences in the lung microbiome of patients with different infections including coccidioidomycosis, a common fungal pneumonia in Arizona.ResultsWe observed patterns of dysbiosis in the lung microbiome during active fungal infection. Patients with active coccidioidomycosis infections had an overabundance of Malassezia, Epicoccum, and Penicillium species in the fungal communities and bacteria in the classes Bacilli, Bacteroidia, Clostridia, and Gammaproteobacteria. Patients with disseminated coccidioidomycosis showed evidence of extreme dysbiosis in the lung microbiome with a significant overabundance of Malassezia and Bacilli. We also observed differences in the fungal communities of patients with an active Candida albicans infection, with an overabundance of the genera Candida and Nakaseomyces. Additionally, we observed a decrease in diversity in the lung fungal communities in patients with an active Coccidioides or Candida infection but no difference in the bacterial community.DiscussionThese compositional changes in the lung microbiome during an active Coccidioides spp. infection associated with shifts in the fungal community. This is the first study to examine how these fungal pathogens affect the lung microbial community of humans.